2020
DOI: 10.1080/21645515.2020.1829315
|View full text |Cite
|
Sign up to set email alerts
|

Assessing COVID-19 vaccine literacy: a preliminary online survey

Abstract: The COVID-19 infodemic can be countered by scientific evidence, clear and consistent communication, and improved health literacy of both individuals in need of information and those providing it. A rapid online survey was carried out to evaluate vaccine literacy (VL) skills in the general population and perceptions about COVID-19 vaccine candidates, along with behavior and beliefs about current vaccinations. Observed VL levels were consistent with previous observations – where comparable self-reported tools we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
308
5
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(342 citation statements)
references
References 21 publications
22
308
5
7
Order By: Relevance
“…In this review, 28 studies depicted the sociodemographic factors associated with public attitudes toward the COVID-19 vaccination. Coherent to findings from the literature [78], the most common factors found to influence vaccine acceptance at the microlevel were age, educational level, gender, race, and income status [23][24][25][26][27][28][29][30][31][32][33][34][35][36][44][45][46][47][48][49][50][51][52][53]63,65,68,[71][72][73]. More willingness to receive a vaccine was reported in the older age group [23,25,27,31,34,35,38,53,65], while resistance, hesitancy, and lack of intention to be vaccinated emerged in the younger age group [29,35,51].…”
Section: Discussionmentioning
confidence: 98%
“…In this review, 28 studies depicted the sociodemographic factors associated with public attitudes toward the COVID-19 vaccination. Coherent to findings from the literature [78], the most common factors found to influence vaccine acceptance at the microlevel were age, educational level, gender, race, and income status [23][24][25][26][27][28][29][30][31][32][33][34][35][36][44][45][46][47][48][49][50][51][52][53]63,65,68,[71][72][73]. More willingness to receive a vaccine was reported in the older age group [23,25,27,31,34,35,38,53,65], while resistance, hesitancy, and lack of intention to be vaccinated emerged in the younger age group [29,35,51].…”
Section: Discussionmentioning
confidence: 98%
“…An investigation carried out via the web in Italy in September 2020 has shown that only 54% would have accepted to receive a COVID-19 vaccine (data collected by an ordinal scale) [10]. On the contrary, we observed a high proportion (>90%) willing to get vaccinated from both the online cross-sectional surveys conducted in June 2020 and January 2021, where data were gathered by the means of a nominal variable (affirmative or negative replies) [2].…”
Section: Discussionmentioning
confidence: 67%
“…Answers were rated by a forced 4 point Likert scale for frequency. As in previous studies using a similar scale [2,4,5], the score was obtained from the mean value of the answers to each item (range 1 to 4), a higher value corresponding to a higher vaccine literacy level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the specific case of COVID-19, this results in the overload of information and misinformation about the pandemic in traditional media, but especially in social media/digital social networks, namely its origin, transmission, diagnosis and treatment in a pandemic context, among other negative limitations. This naturally hampers the combat against this pandemic, both preventatively and curatively, generating higher uncertainty (Naeem & Bhatti, 2020;Biasio et al, 2020;Anwar et al, 2020;Amit Aharon, Ruban, & Dubovi, 2020;Li & Liu, 2020;Halat et al, 2020;Al-Zaman, 2020;Abdulai, Tiffere, Adam, & Kabanunye, 2021;Stokken & Børsen, 2020). In this regard, Peters and Besley (2020) argue that,…”
mentioning
confidence: 99%